The Influence of Inquiry-Based Science Issues Learning on Practical Skills of Junior High School Students in Environmental Pollution Topic (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
Inquiry-based science issues approach facilitates the development of scientific skills through research activities on surrounding science issues. The purpose of this research was to understand the influence of Inquiry-based science issues on practical skills of Junior High School students. This research employed quasi-experimental research method, equipped with pre-test, post-test non-equivalent control group design. The sample of sixty junior high school students in Yogyakarta was picked for this study.Â The instruments used were observation sheets on practical skills, practical skills test, and instructional learning sheets. The data collected were analyzed using N-Gain, percentage, and Analysis of Covariate (ANCOVA) at 0.05 significance level. The result revealed that Inquiry Science Issues was more effective in fostering studentsâ€™ practical skills than the scientific approach. There was a significant effect of treatment on studentsâ€™ practical skills while no interaction between approach and prior knowledge of students. Moreover, the data of practical skills through the observation sheets in the experimental class had higher percentage compared to the control class, 80.36%, and 70.61% respectively.